Fetal central nervous system anomalies: When should we offer exome sequencing?. (20th April 2022) - Baptiste, Caitlin; Mellis, Rhiannon; Aggarwal, Vimla; Lord, Jenny; Eberhardt, Ruth; Kilby, Mark D.; Maher, Eamonn R.; Wapner, Ronald; Giordano, Jessica; Chitty, Lyn
Abstract: Objective: To investigate the detection of pathogenic variants using exome sequencing in an international cohort of fetuses with central nervous system (CNS) anomalies. Methods: We reviewed trio exome sequencing (ES) results for two previously reported unselected cohorts (Prenatal Assessment of Genomes and Exomes (PAGE) and CUIMC) to identify fetuses with CNS anomalies with unremarkable karyotypes and chromosomal microarrays. Variants were classified according to ACMG guidelines and association of pathogenic variants with specific types of CNS anomalies explored. Results: ES was performed in 268 pregnancies with a CNS anomaly identified using prenatal ultrasound. Of those with an isolated, single, CNS anomaly, 7/97 (7.2%) had a likely pathogenic/pathogenic (LP/P) variant. This includes 3/23 (13%) fetuses with isolated mild ventriculomegaly and 3/10 (30%) fetuses with isolated agenesis of the corpus callosum. Where there were multiple anomalies within the CNS, 12/63 (19%) had LP/P variants. Of the 108 cases with CNS and other organ system anomalies, 18 (16.7%) had LP/P findings. Conclusion: ES is an important tool in the prenatal evaluation of fetuses with any CNS anomaly. The rate of LP/P variants tends to be highest in fetuses with multiple CNS anomalies and multisystem anomalies, however, ES may also be of benefit for isolated CNS anomalies. Key points: What's already known about this topic? In fetuses with a structural abnormality and normal karyotype and chromosomal microarray, exome sequencing can provide additional diagnostic yield. The role of exome sequencing in fetuses with anomalies specific to the central nervous system remains unclear. What does this study add? This study supports the importance of including whole exome sequencing in the workup of fetuses affected by CNS anomalies, even if the CNS anomaly is found in isolation.